The relationship between watermelon consumption and sarcopenia in an elderly general population: findings from the Tianjin chronic low-grade systemic inflammation and health study - Wang, Xuena; Yang, Yang; Yin, Lin; Fang, Yufei; Mei, Qi; Niu, Kaijun (Frontiers in Nutrition, 2025)
BackgroundSarcopenia, a progressive skeletal muscle disorder characterized by accelerated loss of muscle mass, strength, and function, affects 10–16% of elderly individuals globally, posing a significant public health challenge. Nutrition is crucial in mitigating sarcopenia progression, with research increasingly focusing on whole foods rather than isolated nutrients. Watermelon emerges as a potentially beneficial functional food due to its high content of L-citrulline, which may support muscle health through various biological mechanisms.MethodsThis population-based cross-sectional study was conducted in Tianjin, China, and analyzed 3,733 elderly participants. Sarcopenia was diagnosed using Asian Working Group for Sarcopenia criteria. Watermelon consumption was assessed using a validated semi-quantitative food frequency questionnaire, categorizing participants into three groups: “almost never,” “≤1 time/week,” and “≥2–3 times/week.” Multiple logistic regression models adjusted for demographic factors, lifestyle variables, medical history, and dietary patterns.ResultsSarcopenia prevalence was 12.6% among participants (median age: 65.8 years). Compared to non-consumers, participants consuming watermelon ≤1 time/week had 28% lower odds of sarcopenia (odds ratio [OR] = 0.72; 95% confidence interval [CI]: 0.54–0.95), while those consuming ≥2–3 times/week had 51% lower odds (OR = 0.49; 95% CI: 0.29–0.79), showing a significant inverse dose–response relationship (p < 0.001).ConclusionHigher watermelon consumption was associated with lower sarcopenia prevalence in elderly Chinese adults. As this was a cross-sectional study, the findings indicate associations rather than causality, and reverse causation cannot be ruled out. Bioactive compounds in watermelon, such as L-citrulline, may be associated with muscle protein synthesis, meriting confirmation in future longitudinal and interventional studies.